A Corpus-Based Approach To The Use Of Grammatical Metaphor In Academic Writing: Distinguishing The Abstract Complexity Written In Linguistic And Science - Katriana, Darryl (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2024)
The objective of this research was to find out the types of grammatical metaphor in experiential function that are mostly used in both of the articles and to describe the distinguish of abstract written in linguistic and science article. The descriptive qualitative method was applied in this study of grammatical metaphor specifically in experiential function in the abstract written in linguistic and science. The findings were shown that the material processes in those types were most frequently applying on the linguistic and science abstract. It was showed that there were 12 categories (7 material process in linguistic article or 77.8% and 5 material process in science article or 62.5%) out of 35 categories of the sentences from both abstract selected. The use of from material process was dominating the abstract of linguistic and science, and it had been as the characteristics of the abstract in the experiential function specially in material process. The results of this research could be extra information in studying grammatical metaphor that focused on ideational metaphor that is experiential function and logical function, interpersonal metaphor, and textual metaphor.